Pemberdayaan Mahasiswa Sebagai Salah Satu Komponen Dalam Usaha Bela Negara Di Bidang Pencerdasan Kehidupan Berbangsa Dan Bernegara Dalam Konteks Negara Kesatuan Republik Indonesia - Irwan Triadi; Annisa Aulia Rahma (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
State defense is an effort made by components within a country to defend, uphold and maintain sovereignty and independence both territorially and in the lives of the people within it. Both outwardly and inwardly. Efforts to defend the country are based on a high sense of nationalism and national and state awareness, therefore efforts to defend the country are not only carried out by certain components within a country, but also by all components that have merged into one within a country as concrete evidence. that an individual has truly become part of a country. Students are no exception. This journal will discuss cases related to the essence of efforts to defend the country on a non-military basis carried out by students through efforts to educate the nation's life through normative juridical analysis methods. This method focuses on further literature study through sources published by legal experts so that their knowledge can be justified. In the process of preparing this journal, the author used a normative juridical analysis method. In general, the normative juridical analysis method is a type of research that focuses on further literature studies, whether from journals, articles, or secondary materials such as laws or literature by legal experts that have been published previously and whose scientific knowledge can be justified. The outcomes that the author hopes for readers through this journal are: 1) Creating awareness in efforts to defend the country, 2) Optimizing the role of students as one of the components of defending the country, 3) Inviting readers to become active participants in efforts to defend the country, 4 ) Raising issues related to the intelligent life of the nation and state in accordance with the goals of the Indonesian nation. It is hoped that this article can open and broaden readers' insight regarding awareness of national defense which is not only carried out on a military basis, but can also be carried out on a non-military basis. For example, through actions to educate the nation's life to support the survival of the nation, by creating future generations of the nation who are superior, competitive and able to compete on the world stage.